2014
DOI: 10.1364/josab.31.002045
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the source of enhancement in experimental continuous variable quantum illumination

Abstract: A quantum illumination protocol exploits correlated light beams to enhance the probability of detection of a partially reflecting object lying in a very noisy background. Recently a simple photon-number-detection-based implementation of a quantum illumination-like scheme was provided in Phys. Rev. Lett. 101, 153603 (2013), where the enhancement was preserved despite the loss of nonclassicality. In the present paper, we investigate the source for quantum advantage in that realization. We introduce an effective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Losses and noise background do not affect the quantum enhancement. The improvement with respect to the classical case is also related to the mutual information of the twin beams which exceeds the one of classically correlated beams [7]. This application does not require entanglement, however it relies on non-classical correlations in the sense of the non-classicality of the Glauber-Sudarshan P function as demonstrated from the fact that the Cauchy-Schwartz parameter is always ε > 1.…”
Section: Quantum Enhanced Detection Of Reflective Target In a Noisy Ementioning
confidence: 98%
See 2 more Smart Citations
“…Losses and noise background do not affect the quantum enhancement. The improvement with respect to the classical case is also related to the mutual information of the twin beams which exceeds the one of classically correlated beams [7]. This application does not require entanglement, however it relies on non-classical correlations in the sense of the non-classicality of the Glauber-Sudarshan P function as demonstrated from the fact that the Cauchy-Schwartz parameter is always ε > 1.…”
Section: Quantum Enhanced Detection Of Reflective Target In a Noisy Ementioning
confidence: 98%
“…03011-p. 7 If the phase between the TWB and the coherent beams is chosen properly, and for an initial phase shift of the two interferometers close to zero (but not exactly zero), as for example φ 1 = φ 2 ∼ 0.001, the use of TWB state leads to the result that the contribution to the uncertainty coming from the photon number noise is U (0) TWB ∝ 1/λ (when μ λ 1), representing a great improvement in accuracy of the interferometric scheme.…”
Section: Icnfp 2014mentioning
confidence: 99%
See 1 more Smart Citation
“…Quantum illumination (QI) [1][2][3][4][5][6][7][8][9] uses entanglement to outperform the optimum classical-illumination (CI) system for detecting the presence of a weakly-reflecting target that is embedded in a very noisy background, despite that environment's destroying the initial entanglement [10]. With optimum quantum reception, QI's error-probability exponent-set by the quantum Chernoff bound (QCB) [13]-is 6 dB higher [4] than that of the optimum CI system, i.e., a coherent-state transmitter and a homodyne receiver.…”
mentioning
confidence: 99%
“…[6], we demonstrate that the non-Gaussian entanglement state derived from the biside photon subtraction could further extend the regime in which quantum illumination outperforms its classic variances. More recently, a quantum illumination experiment, based on photon number detection [7], has been carried out and has shown that illumination with a quantum protocol has clear advantages with respect to classical illumination [8].…”
mentioning
confidence: 99%